Metamorphoses Creative-Developmental Fairy Tale Therapy Against the Dangers of the Internet. A Series of Activities for Young Undergraduate Students - Godó, Irén (Central European Journal of Educational Research, 2021)
This paper is about the practical application of Metamorphoses creative-developmental fairy tale therapy, which is presented based on a three-session Metamorphoses creative-developmental fairy tale therapy session. The sessions were conducted between April and May 2021, among students (n=24) of the University of Debrecen, who were previously not familiar with fairy tale therapy, nor with the works of Ildikó Boldizsár. Through the media environment of the session, we also reflected together on the effects of internet consumption and the dangers of the internet. The study highlights the students' attitudes towards this method and their participation and activity in the online space. The experiences gained during the 3 sessions and the feedback of the students appear as a guideline to conclude the study. The practical application of the Metamorphoses creative-developmental fairy tale therapy will show whether this methodology has a role to play in higher education.